Fathers' Perceptions of the Availability of Flexible Working Arrangements: Evidence from the UK. (December 2021) - Cook, Rose; O'Brien, Margaret; Connolly, Sara; Aldrich, Matthew; Speight, Svetlana
A conditional right to request flexible working arrangements (FWAs) has existed for most UK employee parents since 2003. However, there are growing concerns about access, particularly among fathers. Using nationally representative data from the 2015 UK Household Longitudinal Survey, this article examines fathers' perceptions of the availability of hours reduction, schedule flexibility and working from home. Results show that almost one-third of fathers believe that FWAs that reduce working hours are unavailable to them, compared with one-tenth of mothers. There are no gender differences in perceptions of availability of schedule and location flexibility. Among fathers, those with lower education levels, in lower status occupations, working in the private sector and in workplaces that do not have trade union presence are more likely to believe that FWAs are unavailable. Therefore, even though most employees now have the right to request FWAs, a significant minority of fathers do not perceive FWAs to be available to them.